MEASURING EQUITY AND SOCIAL SUSTAINABILITY THROUGH ACCESSIBILITY TO PUBLIC SERVICES BY PUBLIC TRANSPORT. THE CASE OF THE METROPOLITAN AREA OF VALENCIA (SPAIN) - María-Dolores PITARCH GARRIDO (European Journal of Geography)
Spatial equity in complex spaces such as metropolitan areas is a very interesting subject for research, particularly in view of its enormous potential public policy applicability. An approach to the subject based on the population's access to essential public services (education, health care and social services) is proposed. Geographic Information System (GIS) tools have made a powerful contribution to the ease with which both spatial and statistical data can be handled. The study covers the Metropolitan Area of Valencia, in Spain. It is based on the location of public facilities and the population's ability to move around using public transport. Its objective is to give a general overview of the situation and point to problem zones, with the aim of suggesting answers for these that could help to improve social and spatial sustainability and equity in this metropolitan area.